2-D Strength Prediction of Single-row Multi-bolted Joints Woven Fabric Kenaf Composites - Supar, Khairi; Hilton Ahmad, Hilton (International Journal of Engineering and Technology, 2018)
Implementation of multi-bolts arrangements in structures connections are commonplace in steel design to allow for joint efficiency and stronger connections. Woven fabric kenaf fibers are potentially used as reinforcement in composite materials due to excellent specific strength, renewability and less hazardous during handling as compared to commercial fibers. A two-dimensional Extended Finite Element Method (XFEM) framework of single-row multi-bolted joints has been developed to study the stress distribution and predict the joint bearing stress at failure. Stress distribution among adjacent bolts were compared along the hole boundary and net-tension plane, suggesting net-tension failure occurred at end-bolt. The predicted bearing strength from finite element modelling are validated against experimental framework. The testing series under investigated consists of four datasets from single-row 2 bolts and 3 bolts single-lap joints.Â Current study showed that the XFEM models demonstrated good agreements with the experimental results.Â Â